THE SINGLE AND PLURAL PHRASES IN MATTHEW 4:16 AND THEIR MEANINGS - Adi Putra (Scriptura Indonesia, 2021)
Matthew 4:16 finds both singular and plural phrases. This phrase is very interesting to study because the context of this verse is in Galilee, a place where Jesus spent most of his time serving. Through qualitative research with an exegetical study approach, the researcher found that the results and conclusions were that the purpose of singular and plural phrases in these verses was: a singular phrase for Jews and a plural phrase for other nations. Thus, it can provide the theological understanding that Jesus' mission in Galilee was not only for the Jews who were there, but also for other nations who had long settled there even before the time of Jesus.